Integrating telepsychiatry services in a care setting in Kenya: a case report. (May 2022) - Njenga, Frank; Ongeri, Linnet; Nguithi, Anna; Anundo, Jacqueline; Mugane, Maryann; Kimari, Zawadi; Mbugua, Gathoni; Kaigwa, Cushny; Atwoli, Lukoye
Abstract : Globally, health providers and patients alike have been forced to adapt rapidly to the use of telemedicine during the COVID-19 pandemic. Although telepsychiatry has been tested and found just as effective as face-to-face care, there still remains little uptake of this form of care provision in sub-Saharan Africa. This case study highlights the use of telepsychiatry in a previously telemedicine-naive private mental health facility in Kenya. We describe the challenges and lessons learned from the experience. We conclude on the need to test the effectiveness and acceptability of this mode of therapy in sub-Saharan Africa.